1979
DOI: 10.1136/ard.38.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of treatment with penicillamine after proteinuria.

Abstract: SUMMARY Penicillamine has been successfully reintroduced and continued for a minimum of 13 months in 5 patients who developed proteinuria during the first course of the drug. The daily maintenance dose during the second course was 150-250 mg taken midway between 2 meals. Proteinuria did not recur; no significant excretion of fibrin degradation products occurred; complement, urea, creatinine, and serum albumin remained within normal limits. Urine microscopy showed no abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Jaffe [152] reported that reintroduction of D-penicillamine in patients with drug previous induced proteinuria, starting with a daily dose of 250 mg was usually followed by areturn of proteinuria at about the same time and at about the same cumulative dose as on the first occasion. However, Hill et al [135] reported successful reintroduction and continuation for a minimum of 13 months in 5 rheumatoid arthritis patients who developed proteinuria during the first course of the drug. They instituted the "go slow, go low" method of laffe [153], starting with a daily dose of 50 mg and increasing by monthly increment of 50 mg to a maintenance dose of 150 mg daily.…”
Section: Therapy and Prognosis Of Proteinuriamentioning
confidence: 96%
See 2 more Smart Citations
“…Jaffe [152] reported that reintroduction of D-penicillamine in patients with drug previous induced proteinuria, starting with a daily dose of 250 mg was usually followed by areturn of proteinuria at about the same time and at about the same cumulative dose as on the first occasion. However, Hill et al [135] reported successful reintroduction and continuation for a minimum of 13 months in 5 rheumatoid arthritis patients who developed proteinuria during the first course of the drug. They instituted the "go slow, go low" method of laffe [153], starting with a daily dose of 50 mg and increasing by monthly increment of 50 mg to a maintenance dose of 150 mg daily.…”
Section: Therapy and Prognosis Of Proteinuriamentioning
confidence: 96%
“…The dose was held at 150 mg/day for 4 months and thereafter increased by 50 mg at 3-months intervals if disease remained active. Proteinuria did not recur, and improvement of disease was shown in all 5 patients [135]. Helen et al [67] advocated withholding DpeniciIIamine if there is (1) proteinuria of 2 + on the dipstick, (2) persistent (longer than 3 weeks) proteinuria of 1 +, (3) if there are red cell casts, white cell casts, or hyaline casts present, or (4) if red cells > 10 per high power field are present.…”
Section: Therapy and Prognosis Of Proteinuriamentioning
confidence: 97%
See 1 more Smart Citation
“…After stopping D-penicillamine, proteinuria resolved in 3, progressive proteinuria was seen in one patient, mild proteinuria persisted in 4 others, with the persistence of proteinuria being seen up to 27 mo after stoppage of D-penicillamine[ 68 ]. Some studies have been done to see whether D-penicillamine can be resumed after the resolution of proteinuria[ 69 ]. In one of the studies in rheumatoid arthritis patients, D-penicillamine was re-introduced after 3 mo of resolution of proteinuria at a low dose of 50 mg/d, escalated to a maximum of 250 mg/d, showed that none of them had a relapse of proteinuria.…”
Section: Management Difficultiesmentioning
confidence: 99%